Roles of extrahepatic lipolysis and the disturbance of hepatic fatty acid metabolism in TNF-α -induced hepatic steatosis. (1st January 2019) - Yang, Rui; Guan, Min-Jie; Zhao, Ning; Li, Ming-Jun; Zeng, Tao
Abstract: Our previous study showed that both Kupffer cell eliminator (GdCl3 ) and tumor necrosis factor α (TNF-α) receptor antagonist (etanercept) could partially attenuate binge drinking-induced liver steatosis. Herein, we extended the study by directly investigating the roles of TNF-α on the hepatic fat levels in mice and in HepG2 cells, and explored the underlying mechanisms. SPF male ICR mice were exposed to TNF-α (0.166 mg/kg body weight) with or without phenylisopropyl adenosine (PIA, an anti-lipolytic drug) for 1.5, 3, 6, and 24 h. We found that TNF-α treatment resulted in hepatic triglyceride (TG) elevation at 6 h time point, which was blocked by PIA. TNF-α led to the activation of extrahepatic lipolysis demonstrated by the increase of serum free fatty acid (FFA) level, and the increased protein levels of adipose triglyceride lipase (ATGL) and phosphorylated hormone-sensitive lipase (HSL) in mice epididymal adipose tissues, but had no significant effects on the protein levels of sterol regulatory element binding protein 1c (SREBP-1c) and peroxisomal proliferator activation receptor α (PPAR-α) in mice liver. The in vitro study showed TNF-α treatment could not result in elevation of TG in HepG2 cells, although it indeed brought about a slight activation of SREBP-1c. These results support the hypothesis that TNF-α might make a small contribution to ethanol-induced fatty liver by stimulating extrahepatic lipolysis.